An ensemble of Clustering Algorithms Using Different Distance Metrics for Network Traffic Analysis of Companies - Baituma, Bissarinov; Lakhno, Valeriy; Kozlovskyi, Valeriy; Redko, Denys; Desiatko, Alona; Yaremych, Valentyn (Informatica, 2025)
The network traffic analysis problem in large companies utilizing Big Data is considered. An ensemble of clustering algorithms based on Bayesian probability updating employing various distance metrics and adaptive weighting is proposed. An exponential dependence was applied in the weight calculation to enhance differentiation between algorithms. This enhanced the method’s sensitivity to the quality of individual models. The developed approach was tested on open datasets CIC-IDS2017, UNSW-NB15, and CTU-13. The results demonstrated a consistent improvement in clustering quality, with ARI and NMI values reaching 0.78 and 0.75, respectively. The result surpasses the performance of baseline methods (K-means, DBSCAN, classical ensembles). The proposed method demonstrated linear scalability and is applicable for analyzing high-volume corporate network traffic. The results obtained confirmed the practical value of integration into monitoring and anomaly detection systems.